Literature Review: Pemanfaatan Buku Kesehatan Ibu dan Anak (KIA) serta Potensi Pengembangan Selanjutnya - Sugiarti Sugiarti; Yeni Rustina; Defi Efendi (Politeknik Kesehatan Tanjung Karang, 2020)
The period of 1000 days of life plays an important role in determining the quality of children's growth and development. Accessibility of quality health services through the MCH handbook is an important strategy for improving maternal and child health. The purpose of this review is to present an overview of the use and usefulness of the possession of a specific MCH handbook on maternal, infant and child outcomes, as well as the potential for further research development. The method of systematic study and study search through the ProQuest, EBSCOhost, and Scopus databases, with the keywords maternal and child health handbook, home based record, mother, newborn, infant, and child, published from January 2008 to October 2018. Furthermore, filtering of articles and data abstraction. A total of 56 articles on the use of the MCH handbook that met the eligibility/inclusion criteria were screened, and 16 articles were selected for a systematic review. The variety of existing studies, has proven the benefits, functions, and effectiveness of the MCH handbook on the health of mothers, infants, and children. The categories of use and use of MCH handbook are integrated with home-based records, namely as an effective tool to facilitate improvement in health-seeking behavior; continuous care; health communication, information and education; as well as home based health records. In order to fill the gap, further research can be directed at evaluating especially premature babies/LBW as part of a population of newborns with high risk. The use of digital technology in improving the implementation of interventions and the accessibility of MCH handbook is also important to be developed.